COMPARATIVE ASSESSMENT OF AERODYNAMIC PROPERTIES OF SALBUTAMOL PRESSURIZED METERED DOSE INHALERS - N. A. Lyapunov; E. P. Bezuglaya; V. A. Bovtenko; Yu. M. Stolper (Разработка и регистрация лекарственных средств, 2019)
The aerodynamic properties of the developed generic product Salbutamol metered dose inhaler 100 μg/dose and Salbutamol-Teva metered dose inhaler 100 μg/dose using apparatuses A, C, D and E in accordance with the general article 2.9.18 of the European Pharmacopoeia have been studied. In vitro equivalence of the generic product and the comparator with regard to such aerodynamic characteristics as the fine particle dose, the particle size distribution, the relative amount of salbutamol passed through the apparatus stages, the mass median aerodynamic diameter (MMAD), and the geometric standard deviation (GSD) has been shown. It is shown that the device A is useful for testing of the respirable fraction, and the apparatuses D and E are suitable for the assessment of the particle size distribution, MMAD and GSD.